Investigating differential item functioning to validate a thinking skills learning progression for students with intellectual disability and autism spectrum disorder. (2021) - Kamei, Toshiko; Pavlovic, M.
Highlights: A thinking skills learning progression for students with disability was derived. Students with ASD had distinct strengths and challenges in thinking skills. The order of skill development of students with ID and ASD were matched. Differences in thinking skills of students with ASD were insignificant. Abstract: Thinking skills are recognised as vital components of improved academic and life outcomes. This study's purpose was to develop an assessment of thinking skills for students with intellectual disabilities (ID) and autism spectrum disorder (ASD). A pool of items was developed based on review of research combined with expert judgement. Items were trialled with teachers of 864 students. Within this sample, 616 students were diagnosed with ID, of whom 301 had ASD. Differential item functioning, as part of a partial credit item response model analysis, was used to validate a skills progression for these groups of students. Implications include arguments for teachers to provide instruction in thinking skills to students with less focus on a label or diagnosis but ability.